SME open innovation for process development: understanding process-dedicated external knowledge sourcing (2020)
Small and medium enterprise (SME) open innovation has received attention only for new product development, overlooking the fact that process innovation is a strategy commonly pursued by SMEs which requires organizing search strategies or external knowledge sourcing for that purpose. Focusing on 3,348 process-oriented innovative SMEs, defined as those that usually and primarily only introduce process rather than product innovation, this study empirically identifies key external sources of SME innovation for process technologies, linking open innovation to SME performance, and highlighting a very important distinction to literature focused on product development. The results contribute to the literature on SME open innovation.